2019
DOI: 10.1002/anie.201900829
|View full text |Cite
|
Sign up to set email alerts
|

Towards DNA Nanomachines for Cancer Treatment: Achieving Selective and Efficient Cleavage of Folded RNA

Abstract: Despite decades of effort, gene therapy( GT) has failed to deliver clinically significant anticancer treatment, owingi np art to lows electivity,l ow efficiency,a nd poor accessibility of folded RNAt argets.H erein, we propose to solve these common problems of GT agents by using aD NA nanotechnology approach. We designed ad eoxyribozymebased DNAm achine that can i) recognizet he sequence of ac ancer biomarker with high selectivity,i i) tightly bind as tructured fragment of ah ousekeeping gene mRNA, and iii)cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…Such DNA constructions can be easily assembled by annealing the constituent DNA strands (e.g., T1, T2, and T3 in Scheme ). We found that the DNA machine can recognize both the marker sequence and targeted RNA fragment with high selectivity under near physiological conditions . The fundamental principles of superior selectivity of multicomponent in comparison with monolith hybridization probes was comprehensively discussed earlier .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Such DNA constructions can be easily assembled by annealing the constituent DNA strands (e.g., T1, T2, and T3 in Scheme ). We found that the DNA machine can recognize both the marker sequence and targeted RNA fragment with high selectivity under near physiological conditions . The fundamental principles of superior selectivity of multicomponent in comparison with monolith hybridization probes was comprehensively discussed earlier .…”
Section: Introductionmentioning
confidence: 83%
“…Another factor contributing to decreased RCDZ efficiency is folded RNA structure, which can significantly reduce accessibility of targeted sequences . Indeed, when 8–17 was used to cleave a long folded RNA substrate, its activity dropped more than 100 times in comparison with cleavage rate of a 19‐nt RNA substrate .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] Not only do these RNA-cleaving DNAzymes specifically recognize their target RNAs ubstrates through Watson-Crick base pairing,they are also highly specific with regards to the metalion cofactors,thus making them very useful tools in chemical biology for sensing metal ions [8] and regulating gene expression. [10] To activate DNAzyme activities by external stimuli, caged DNAzymes containing light-responsive modifications have been developed for light-dependent control of intracellular metal-ion biosensing or gene regulation. [10] To activate DNAzyme activities by external stimuli, caged DNAzymes containing light-responsive modifications have been developed for light-dependent control of intracellular metal-ion biosensing or gene regulation.…”
mentioning
confidence: 99%